Cartographic update through image digital processing by Mathematical Morphology techniques - Stroppa, R. G. [UNESP]; Leonardi, F. [UNESP]; Frigato, R. [UNESP]; Silva, E. [UNESP] (My University, 2009)
Amongst the many tools of Digital Image Processing - PDI, this work presents the application of the Mathematical Morphology theory (MM), which consists in describing geometric structures in digital images in a quantitative manner using morphologic detectors of edges and afterwards image filtering. Morphological operators' application for the detection of Água Vermelha barrage contours is carried out in this work. It shows results evidencing that MM techniques are successfully applied for features extraction in digital images, especially for calculation of reservoirs' flooded area. Furthermore, Mathematical Morphology theory potential in Cartography is evidenced due to its easy application, low cost and trustworthy results.
Keywords: Cartographic update; Digital Image Processing; Mathematical morphology; Remote sensing